Shaping Ahwaz’ transnational oil modernity: at the crossroads of oil flows and international planning exchanges - Sarkhosh, Rezvan (International Planning History Society Proceedings, 2018)
Through the lens of flows of petroleum, a key commodity of the 20th century, to revisit local urban histories, this paper contributes to the growing literature on transnational and cross-cultural urbanism. It argues that oil created a unique network of international stakeholders (British, German, and American), from various disciplines and professions (engineering, architecture and urban planning) who collaborated to build modern industrial cities adjacent to Iranian oil fields, much of which were found in previously uninhabited areas. Focussing on the development of the southern city of Ahwaz between 1908 and the start of the Iran-Iraq war in 1980, this paper explores how catering to the different facets of the oil industry (oil extraction, transformation, administration, infrastructure and retail), created a cosmopolitan built environment composed of a variety of architectural styles and urban planning approaches. The diverse actors who co-shaped Iran’s oil cities also impacted people's lifestyles through new spatial arrangements. These international actors transformed and localized the global flows of ideas and created native processes of modernization. Albeit their good intentions, many of these actors failed to respond to the needs of the people on the ground and thereby contributed to creating social gaps among different strata of the society. Cosmopolitanism in architecture was thusly limited to styles and forms, rather than a truly just and democratic cosmopolitan society.